Action research in the field of societal entrepreneurship. Building participative relationships. - Erik Rosell (European Regional Science Association (ERSA), 2010)
Research on entrepreneurship has taken "the linguistic turn" inspired by postmodernism, narrative methods and a social constructionist perspective. This movement is particularly evident in the Scandinavian entrepreneurship research tradition (Hjorth, 2008). As a consequence, many of the inhibitions that traditionally have hindered researchers from getting close to their study objects are removed. Postmodernism teach us that the reseracher doesn't have to be a distant, observing and disembodied narrator claiming universal and general knowledge. As Gergen (2003) notes, the basic assumptions that comes with a social constructionist perspective makes action research both a legitimate as well as promising pathway for further experimentation and development in qualitative research. He also notes that action research is gaining a steady momentum within the social sciences. Action research differs from both basic and applied social research in terms of people's involvement in the research process. With this involvement follows an integration of action with research, and a practice-based nature of the knowledge that is entailed (Park, 2001). Knowledge is seen to bee enriched through direct involvement, intervention or insertion in processes of social action. The ambition is to arrive at a subject/ subject relationship with the ones beeing "studied", combining different kinds of knowledge in the research process (Fals Borda, 2001). Although participation is singled out as the main defining character of action research (Reason & Bradbury, 2001) and is widely discussed in the action research literature, relatively few studies deal with building the participative relationship itself. The aim of this paper is to contribute to the knowledge of the relationship building process in action research projects. Based on a description of a co- operation between researchers and practioners, the ambition is to give a detailed account of this process, letting the voices of the researchers as well as the participating co- reserachers/ practioners be heard in the text.
Keywords: 330